The Pengaruh Penerapan Permainan Kucing dan Tikus terhadap Hasil Belajar Lari Sprint - Herdiansyah, Nugie Herdiansyah; Lengkana, Anggi Setia; Sudirjo, Encep Sudirjo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
ABSTRACT This research aims to determine the effect of the game of cat and mouse on speed results in learning to sprint for class V students at SDN Dahniar. This research uses a quantitative pre-experiment method, one group pretest and posttest. Based on the normality test results, it is known that the overall pretest data 0.062 and posttest 0.034 > 0.05 are normally distributed. Then, it was tested using the paired sample T-test, where the average initial test value of the initial test was 2.85 while the final test value was 3.40 so that the average value of both was -0.550 with a sig value of paired T-test samples >0.05, namely 0.142. This shows that there is no influence of the cat and mouse game on the results of the sprint learning speed of class V students at Dahniar State Elementary School, and the cat and mouse game of class V students of Dahniar State Elementary School cannot influence the results of sprint learning speed. The conclusion is that the game of cat and mouse does not influence the results of learning to sprint. Keywords: Games, Influence, Print Running Learning Results